Effect of Incorporation of Silver Nanoparticles on the Tensile Bond Strength of a Long term Soft Denture Liner - Habibzadeh, Sareh; Omidvaran, Arman; Eskandarion, Solmauz; Shamshiri, Ahmad Reza (European Journal of Dentistry, 2020)
Objectives This study aimed at assessing the effect of the addition of silver nanoparticles (SNPs) to a silicone soft liner on its tensile bond strength to denture base resin.Materials and Methods SNPs were added to Mucopren cold cure soft liner in 0 (control), 0.5, 1, 2, and 3 wt% concentrations and bonded in 120 stainless steel molds with processed heat cure acrylic resin blocks. Liner/resin combination samples were divided into two groups. The first half was stored for 2 days in distilled water at 37°C and then subjected to tensile bond strength, while the other half were thermocycled 3000 times before testing. Mean bond strength, expressed in mega pascals (MPa), was determined in the tensile test with the use of a universal testing machine at a crosshead speed of 5 mm/min.Statistical Analysis Data were analyzed using SPSS via one-way analysis of variance test, t-test, and Tukey’s posthoc, at a 95% confidence level (p < 0.05).Results Addition of SNPs and thermocycling both caused a significant reduction in the tensile bond strength of Mucopren to acrylic resin; however, in the thermocycled group, the bond strength increased with the increase in the concentration of SNPs (p < 0.001).Conclusion Addition of SNPs to Mucopren soft silicone liner reduces its tensile bond strength to denture acrylic resin.
Keywords: denture liners; nanoparticles; tensile bond strength